(untitled) (Journal of Hama University, 2024)
ي The current study aims at recognizing the relationship between thinking styles and psychological adjustment for pupils of learning difficulties. The sample consists of 45 male/ female pupils at inclusion schools at Hama city. The study uses the descriptive analytic approach by applying the test of thinking styles according to Sternberg’s theory of Mental Self Government prepared by Rana Sam Amar, and the standard of psychological adjustment prepared by the researcher. The results of the study are: The most prevailing thinking styles for pupils of learning difficulties are: (monarchic, local, executive, hierarchical, conservative, legislative) The least prevailing thinking styles for pupils of learning difficulties are: (global, judicial, liberal). The level of psychological adjustment is low. There is a statistically significant relationship between two thinking styles (conservative, executive) and psychological adjustment, whereas there is no relationship between thinking styles (monarchic, hierarchical, legislative, local, liberal, global, judicial) and psychological adjustment for pupils of learning difficulties. There are statistically significant differences according to thinking styles (hierarchical, legislative, local, conservative) and in the total score of thinking styles for the sake of females. There are statistically significant differences between the average grades on the scale of psychological adjustment according to gender for the sake of females.